2008
DOI: 10.1242/jeb.016832
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity on intestinal bicarbonate secretion and compensatory regulation of acid–base balance inOpsanus beta

Abstract: SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 44 publications
4
95
0
Order By: Relevance
“…A potential caveat to this statement is that E2 could have increased the intestinal absorption of SO 4 2-and the apparent change in fluid absorption is an artefact of lowered intestinal [SO 4 2-] rather than fluid movements. However, assuming that sulphate transport was not affected, and was close to negligible as previously found (Hickman, 1968;Genz et al, 2008), a reduction in the intestinal water absorption can occur for the two reasons described below.…”
Section: Effect Of E2 On Ion and Water Handling Processes In The Intesupporting
confidence: 62%
See 1 more Smart Citation
“…A potential caveat to this statement is that E2 could have increased the intestinal absorption of SO 4 2-and the apparent change in fluid absorption is an artefact of lowered intestinal [SO 4 2-] rather than fluid movements. However, assuming that sulphate transport was not affected, and was close to negligible as previously found (Hickman, 1968;Genz et al, 2008), a reduction in the intestinal water absorption can occur for the two reasons described below.…”
Section: Effect Of E2 On Ion and Water Handling Processes In The Intesupporting
confidence: 62%
“…Hickman (Hickman, 1968) and Genz et al (Genz et al, 2008) have previously used SO 4 2-concentrations in rectal fluid as a surrogate of intestinal fluid absorption based on the assumption that intestinal epithelium is impermeable to MgSO 4 , thus considering it as a potential endogenous marker for water absorption. In the present study, seawater and intestinal [SO 4 2-] for each fish were measured and used to obtain an estimate of fractional water absorption (%) by the intestine by using the formula:…”
Section: Calculations and Data Analysismentioning
confidence: 99%
“…Only three studies measured blood plasma [Cl − ], but none of them found significant changes after exposure to OA-like conditions Green and Jutfelt, 2014;Heinrich et al, 2014). The lack of change in plasma [Cl − ] in marine fish could be due to the difficulty in accurately measuring small changes in [Cl − ] compared with 'background' control levels of 140-200 mmol l −1 (see Genz et al, 2008;Erlacher-Reid et al, 2011;Esbaugh et al, 2016;Lin et al, 2003;Toews et al, 1983;reviewed in Evans et al, 2005). However, it is also possible that the large range of reported values of [Cl − ] reflect species-, life stage-or metabolism-specific differences.…”
Section: Pharmacological Considerationsmentioning
confidence: 99%
“…The intestinal epithelium of marine teleosts displays very low permeability to both of these ions in vitro (Grosell and Taylor, 2007), and they have been used as a reliable proxy for intestinal fluid transport in vivo (Hickman, 1968;Genz et al 2008). Despite this, a direct comparison of measured gravimetrically from Figures 1 and 2 with calculations of based on changes in the corresponding concentrations of Mg 2+ and SO 4 2-in the mucosal saline reveals that these ions do not offer a suitable alternative to either PEG or the gravimetric method of measuring fluid transport in vitro (Table 5).…”
Section: An Alternative To [mentioning
confidence: 99%
“…High molecular weight PEGs (3350-4000) are considered to be poorly absorbed by the intestine (Schedl, 1966;Krag et al 1975; Winne and Gorig, 1982;Furuichi et al 1984;Schiller et al 1997; Grosell and Genz, 2006), and easily determined in biological fluids by direct assay (Malawer and Powell, 1967) or labelling the PEG molecule with a radioisotope such as 3 H or 14 C (Wingate et al 1972;Krag et al 1975). The latter offers the greatest sensitivity and practical advantage, hence radiolabelled PEG has become a common choice in studies of gastrointestinal physiology, such as gut transit and digestibility in ruminants (Till and Downes, 1965;Pickard and Stevens, 1972), drinking rates in fish (Shehadeh and Gordon, 1969;Scott et al 2006;Genz et al 2008), and is widely regarded as a suitable volume marker for studies of intestinal absorption in vivo (Jacobson et al 1963;Schedl, 1966;Maddrey et al 1967;Schiller et al 1997).…”
Section: Introductionmentioning
confidence: 99%